Abundance and ecologic distribution of the shrimp Rimapenaeus constrictus (Crustacea : Penaeidae) on the northern coast of São Paulo State, Brazil - Costa, R. C.; Fransozo, A. (Taylor & Francis Ltd, 2004)
The abundance and ecologic distribution of the shrimp R. constrictus were compared among three different embayments within the northern coast of São Paulo State (23degreesS, 45degreesW); i.e. Mar Virado (MV), Ubatuba (UBA) and Ubatumirim (UBM). Key environmental factors were monitored for a better understanding of the distributional patterns of this species, namely temperature, salinity, depth, organic matter content and texture of sediments. In each bay, six transects were delimited, four parallel to the coastline and the other two in areas adjacent to rocky shores. Monthly samples were taken over a 2-year period (1998 and 1999), using a shrimp fishing boat equipped with double-rig nets. Abundance data were treated separately according to environmental characteristics. A total of 4978 specimens was obtained; 921 at MV, 1948 at UBA and 2109 at UBM. The spatial distribution of R. constrictus differed among bays. Higher abundance values were recorded at areas where silt and clay comprised less than 70% of the sediment. A more diversified sediment at UBM and UBA apparently favours the establishment of this species in the region. Its abundance also followed a seasonal trend, higher during spring and summer when intrusions of cold South Atlantic Coastal Waters (SACW) are frequent, promoting the migration of this shrimp to more sheltered areas. These results suggest that sediment type and temperature are the most important variables affecting the spatial and seasonal distribution of this species.
Keywords: abundance; distribution; shrimp; Penaeidae